Deforesting the forest: Territory and relations in the Argentinean Chaco. - Tola, Florencia C. (Journal of Latin American & Caribbean Anthropology, 2024)
This article examines in depth the nuances of the Toba (Qom) people's territorial claims over the Argentinean Chaco. Ethnographic fieldwork carried out from 1997 to the present in Qom communities in the center of the Argentinean Chaco allows me to analyze the relationships that these communities have maintained and continue maintaining with their territory since their insertion into the regional economy after the Chaco's colonization. The analysis of the alternation of destructive and protective practices shows us the Qom cosmological understandings of human‐forest relations and the ambiguities of their coexistence in which Indigenous people, the nation‐state, nongovernmental organizations (NGO), settlers, and nonhuman beings participate. I propose that the forest, rather than being seen by the Qom people as a common good to be protected amid a planetary crisis, is a relation within relations intersected by ambiguity. This article aims to contribute to studies on the particularities of Indigenous people standing against the destruction that the Anthropocene has brought, avoiding unitary ideas about the Anthropocene.